ANALISIS PENERAPAN BASIS AKRUAL TERHADAP PENYUSUNAN LAPORAN REALISASI ANGGARAN PADA DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN SANGGAU TAHUN 2015 - admin, M. ROMI ADAM HUTAMA RAMBE B41111008 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Accounting is a method of financial record that has widely been used in many field of financial management activities. Accounting is also used in goverment agencies better known as govermental accounting. This reseach aim to find out it the Office of Culture and Tourism Sanggau Regency had applied accrual based accounting in the preparation of financial report in accordance with Goverment regulation No. 71/2010 especially PSAP 02 on the budget realization report, and to find out the difficulties encountered in the implementation of accual based accounting. The method use was descriptive qualitative and the data were collected using interview and document review. Research finding showed that the application of Goverment Regulation No. 71/2010 especially PSAP 02 on accrual based budget realization report had not been applied in the 2015 accounting year. It is suggested should implement Goverment Regulation No. 71/2010 especially PSAP 02 in the preparation of its financial report.. Keyword : Govermental accounting, budget realization reports, accrual basis, goverment regulation No. 71/2010